Geodynamics of rift-plume interaction in Iceland as constrained by new Ar-40/Ar-39 and in situ U-Pb zircon ages - E. Martin; J. Paquette; V. Bosse; G. Ruffet; O. Sigmarsson; M. Tiepolo (Earth and Planetary Science Letters, 2011)
The interaction between a rift zone and a mantle plume leads to exceptional situations in Iceland where the island is 1.5 wider than expected, given the North-Atlantic spreading rate. In order to give a better idea of the timeframe of this evolution, we present 32 new 40Ar/39Ar and in-situ U-Pb dating on zircon from 16 volcanic systems located from the west to east coasts of Iceland. The North Iceland Rift Zone (NIRZ) was initiated at least 12Ma ago. Furthermore, during these last 12Ma, the NIRZ half spreading rate was between 0.7 and 1.2cm/yr and it propagated to the south at a rate of 1.0-1.2cm/yr. The excess width of Iceland can thus not be explained by faster spreading rate in the past. Here we discuss a model that explains the ~200km 'excess' of crust, taking into account the eastward relocation of the rift zone and corresponding older crustal capture over the course of Iceland's geological history. The most recent rift relocation is dated at approximately 6Ma at Snæfellsnes Peninsula in the west, whereas the oldest volcanic systems (15-13Ma) from the extreme north east of Iceland were most likely generated at the Kolbeinsey ridge north of Iceland rather than in the NIRZ itself.The need for rift relocations and crustal capture to explain the width of Iceland strongly suggests that during rift-plume interaction the mantle plume plays an active role. It forces the active rift zone to be frequently relocated by rift jumps above its center leaving inactive rift zones as older synclines in the geological record. This result in an eastward position of the rift zone in Iceland relative to the North Atlantic ridge, and it can be predicted that in a few tens of millions of years the Mid-Atlantic ridge and the Icelandic plume may become decoupled.